Answer :

...............................

${teks-lihat-gambar} vyngo15102004
quantom

Answer:

We need to solve this equation:

[tex]3[-x + (2 x + 1)] = x-1[/tex]

Firstly, we remove the parenthesis, as it's getting summed and it isn't necessary:

[tex]3[-x+2x+1]=x-1[/tex]

Now we operate the brackets:

[tex]3(x+1)=x-1[/tex]

We calculate tha prenthesis:

[tex]3x + 3 = x - 1[/tex]

And finally, we substract x and 3 on both sides. a

[tex]3x + 3 - x - 3 = x - 1 -x - 3[/tex]

[tex]2x = -4[/tex]

[tex]\bold{x = \frac{-4}{2} = -2}[/tex]

Now, we can verify for x = -2:

[tex]3[-(-2)+(2*(-2)+1)]=-3[/tex]

[tex]3[2+(-4+1)]=-3[/tex]

[tex]3[2+(-3)]=3[/tex]

[tex]3[2-3]=-3[/tex]

[tex]3[-1]=-3[/tex] TRUE

Other Questions